Upaya SBY “Menjinakkan” Kelompok Mahasiswa (Analisa Komunikasi Politik dalam Kasus SBY Mengajak Sekelompok Mahasiswa untuk Perjalanan ke Luar Negeri - Lestari Nurhajati (Universitas Al Azhar Indonesia, 2015)
The increasing price of fuel oil (BBM) in Indonesia has always been an issue that raises the pros and cons in the community. Especially the group of students will always be a driving demonstration of the anti- increasing fuel price. But interestingly when the issue of fuel price increase, President Susilo Bambang Yudhoyono (SBY) have a plan to work abroad and accompanied by 80s student representatives from the Student Executive Board (BEM). The situation when assessed with the approach of political communication will encoun- ter an effort of domestication authorities, the President and his team to influence the opini on of the opponent group (students) who considered as a group of demonstrators. One of pressure group on political communication. Domestication in political activities is commonly done by the authorities who felt his posi- tion threatened. This is part of the political hegemony. The excesses of this effort is the divide et impera politics. When examined from a political communications course this approach is not ideal. Political communication is considered successful if there is equality between the commu- nicator and the communicant, without the need to “ degrading “ position of either party